Impact of simulated mechanical hedge pruning and wood age on new shoot demography and return ﬂowering in olive trees - Albarracin, Valeria Mariel (2018)
Key message: More vigorous watersprouts and fewer low vigor shoots form as wood age increases at the cutting points with greater canopy pruning depth in olive trees, which reduces return flowering. Such information is relevant to long-term olive orchard pruning strategies in hedgerows. Abstract: Demographic analysis of growth responses to pruning in fruit trees seeks the quantification of the typology of new shoots originating from the remaining branches. Pruning of hedgerows using mechanical discs is becoming increasingly common in orchards, but little information is available as to how such pruning, which does not discriminate between branch size, wood age at the cutting point, branch type, or position, modifies subsequent new shoot demography. Hence, the experiment described in this study in young olive trees (cv. Arbequina) assessed the following questions: (1) Is the type and growth of new shoots associated with the intensity of mechanical pruning and/or the wood age on which they grow? (2) How many growing seasons does it take for new shoots formed after pruning to flower? The principal hypothesis was that a greater proportion of vigorous watersprouts form compared to low vigor shoots as wood age at the cutting points increases with canopy pruning depth, and that the watersprouts have low flowering potential. Both new shoot growth and return flowering were monitored on exposed supporting wood over several growing seasons after implementing three winter (25W, 50W, and 75W) pruning levels of increasing intensity and one summer pruning (75S) treatment along with an unpruned control (CON). As hypothesized, a greater number and elongation of vigorous watersprouts were found as wood age increased at the cutting points with greater winter pruning intensity, and the watersprouts had low levels of return flowering even 3 full years after pruning compared to the CON. Growth of low vigor shoots was relatively more important than watersprout growth in the severe summer pruning treatment, although 3 years after the summer pruning flowering was not fully recovered. In contrast, the more lightly pruned winter treatments (25W, 50W) did not show significant differences in flowering with the CON at the end of 3 years. Thus, mechanical hedge pruning in olive trees should be light-to-moderate to avoid the formation of watersprouts on older wood, which leads to long-term reductions in flowering.